WEATHERING SEQUENCES OF CLAY MINERALS IN SOILS ALONG A SERPENTINITIC TOPOSEQUENCE - Hseu Z.Y.; Tsai H.; Hsi H.C.; Chen Y.C. (My University, 2007)
There has been limited research on clay mineral transformation in serpentinitic soils under humid tropical conditions. In this study, four soil pedons were selected along a toposequence from the summit (Entisol), shoulder (Vertisol), backslope (Alfisol) to footslope (Ultisol) positions to explore the contributions and the significance of landscape and weathering status of serpentinitic rock with regard to clay mineral transformations in eastern Taiwan. Experimental results indicated that the large amount of dithionite-citrate-bicarbonate-extractable Fe (Fed) and clay in the subsurface horizon were mainly caused by the strong leaching potential from intensive rainfall and weathering of the fine-grained parent rocks. The clay mineralogy reflected the clear weathering trend of the soils along the toposequence: (1) the soils on the summit and shoulder contained smectite and serpentine, which are predominant in the young soils derived from serpentinitic rocks; and (2) vermiculite gradually increased in the relatively old soils on backslope and footslope. The mineralogical transformations observed along the toposequence indicated that chlorite and serpentine, initially present in the Entisol on the summit, weather into smectite and interstratified chlorite-vermiculite in the intermediate soil on the shoulder under strong leaching and oxidizing conditions. Furthermore, vermiculite formed as the major weathering product of chlorite and smectite in the soil developed on the backslope. In addition to vermiculite, kaolinite and quartz formed in the soils on the footslope with the greatest concentration of Fed along the toposequence.
Keywords: CHLORITE; SERPENTINE; SMECTITE; SOIL TAXONOMY; TAIWAN; TOPOSEQUENCE; WEATHERING SEQUENCE